Effectiveness, safety, and treatment pattern of sodium zirconium cyclosilicate in Chinese patients with hyperkalemia: interim analysis from a multicenter, prospective, real-world study (Actualize Study) - Shen, Nan; Zhang, Lihong; Yang, Jing; Lin, Yongqiang; Liu, Xinyu; Cai, Xudong; Cao, Juan; Zhu, Qiang; Luo, Xun; Wan, Xin; Wu, Henglan; Ye, Jianming; et al. (Frontiers in Pharmacology, 2024)
Introduction: Sodium zirconium cyclosilicate (SZC) is a nonabsorbed cation-exchanger approved in China for the treatment of hyperkalemia (HK; serum potassium [sK+] levels >5.0 mmol/L). This is the first real-world study aimed to assess the effectiveness, safety, and treatment patterns of SZC in Chinese patients with HK. Here we present the results of the first interim analysis. Methods: This multicenter, prospective, cohort study included patients aged ≥18 years with documented HK within 1-year before study enrollment day. These patients were followed up for 6 months from the enrollment day after initiating SZC treatment. The treatment was categorized into correction phase (FAS-P1) and maintenance phase (FAS-P2 new and ongoing users). Subgroup analysis was performed in patients on hemodialysis (FAS-H). The primary objective was evaluation of safety profile of SZC; secondary objectives included assessment of treatment patterns of SZC and its effectiveness. Results: Of 421 screened patients, 193, 354, and 162 patients were enrolled in the FAS-P1, FAS-P2, and FAS-H groups, respectively. sK+ levels were reduced significantly from 5.8 mmol/L to 5.0 mmol/L after the correction phase. For the maintenance phase, the mean sK+ levels were maintained at 5.2 mmol/L and 5.0 mmol/L in the FAS-P2 new and ongoing user, respectively, and 5.3 mmol/L in the FAS-H subgroup. A considerable proportion of patients showed normokalemia after 48h of SZC treatment (FAS-P1:51.3%) which was maintained up to 6 months in the maintenance phase (FAS-P2:44%). SZC was welltolerated. Conclusion: SZC was effective and safe for the treatment of HK in real-world clinical practice in China.